1993
DOI: 10.1002/ana.410340117
|View full text |Cite
|
Sign up to set email alerts
|

The effects of X monosomy on brain development: Monozygotic twins discorcant for Turner's syndrome

Abstract: Monosomy for the X chromosome is the most frequent cause of Turner's syndrome, a common clinical syndrome associated with particular physical and neurobehavioral features. The results from comprehensive assessment of prepubertal monozygotic female twins discordant for X monosomy are presented. Zygosity was established with DNA Fingerprinting and no evidence of chromosomal mosaicism was seen in either child. Physical features in the affected twin were relatively mild with respect to the full spectrum of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 39 publications
4
55
1
4
Order By: Relevance
“…The same studies also reported an unexplained enlargement of the parahippocampal gyrus in Down's syndrome (44,45). In Turner's syndrome, the size of the hippocampus has also been reported to be diminished (46).…”
Section: Discussionmentioning
confidence: 72%
“…The same studies also reported an unexplained enlargement of the parahippocampal gyrus in Down's syndrome (44,45). In Turner's syndrome, the size of the hippocampus has also been reported to be diminished (46).…”
Section: Discussionmentioning
confidence: 72%
“…A positron emission tomography study of five adult women demonstrated a glucose hypometabolism in bilateral parietal and occipital regions (Clark, Klonoff, & Hadyen, 1990). Two anatomical MR studies, one with 18 and the other with 30 affected women, demonstrated bilateral reductions in parieto-occipital brain volume, together with other subcortical regions (Murphy et al, 1993; see also Reiss et al, 1993;Reiss, Mazzocco, Greenlaw, Freund, & Ross, 1995). Interestingly, the phenotype of Turner syndrome can differ depending on whether the remaining X chromosome is of paternal or maternal origin (Xm or Xp subtypes; Bishop, Canning, Elgar, Morris, Jacobs, & Skuse, 2000;Skuse, 2000;Skuse et al, 1997).…”
Section: Developmental Dyscalculia and The Ontogeny Of Number Represementioning
confidence: 94%
“…A positron emission tomography study of five adult women demonstrated a glucose hypometabolism in bilateral parietal and occipital regions (Clark, Klonoff, & Hadyen, 1990). Two anatomical MR studies also demonstrated bilateral reductions in parieto-occipital brain volume, together with several other cortical and subcortical regions (Murphy et al, 1993;Reiss et al, 1993;Reiss, Mazzocco, Greenlaw, Freund, & Ross, 1995).…”
Section: Introductionmentioning
confidence: 98%